Connecting China, Latin America and the Caribbean : infrastructure and everyday life - Dussel Peters, Enrique 1965-; Cook, James A.; Alter, Joseph S. (Pitt Latin American series / Catherine M. Conaghan, editor, 2024)
A long history of migration, trade, and shared interests links China to Latin America and the Caribbean. Over the past twenty years, China has increased direct investment and restructured trade relations in the region. In addition, Chinese public sector enterprises, private companies, and various branches of the central government have planned, developed, and built a large number of infrastructure projects in Latin America and the Caribbean, such as dams, roads, railways, energy grids, security systems, telecommunication networks, hospitals, and schools. These projects have had a profound impact on local environments and economies and help shape the lived experiences of individuals. Each chapter in this volume examines how the impact of these infrastructure projects varies in different countries, focusing on how they produce new forms of global connectivity between various sectors of the economy and the resulting economic and cultural links that permeate everyday life